2012
DOI: 10.1097/jto.0b013e31826913f7
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitors Beyond Progressive Disease: A Retrospective Analysis for Japanese Patients with Activating EGFR Mutations

Abstract: Continuous use of EGFR-TKI beyond PD may prolong overall survival compared with switching to cytotoxic chemotherapy in patients with activating EGFR mutations. A prospective study will be needed to confirm our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(64 citation statements)
references
References 25 publications
2
60
0
2
Order By: Relevance
“…Most patients developed disease progression despite an initial response to TKIs. In recent years, continuing molecularly targeted therapy beyond RECIST-PD by physicians has increased in frequency [18,[21][22][23][24]. Moreover, several retrospective studies have suggested that molecularly targeted treatment beyond PD may be feasible and effective in patients with EGFR-positive mutations or ALK positive mutations [18,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Most patients developed disease progression despite an initial response to TKIs. In recent years, continuing molecularly targeted therapy beyond RECIST-PD by physicians has increased in frequency [18,[21][22][23][24]. Moreover, several retrospective studies have suggested that molecularly targeted treatment beyond PD may be feasible and effective in patients with EGFR-positive mutations or ALK positive mutations [18,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Abrupt stopping of the TKI can results in a rapid disease flare resulting in severe deterioration, hospitalisation or death in up to one third of patients [72]. There are still few data concerning the best attitude to have in that situation but available reports suggest that continuing the TKI administration can result in a survival benefit [73,74]. However, the attitude must be adapted to the type of progression: patients relapsing on a single metastatic site may benefit from an aggressive treatment of the metastases (especially if these are localised in areas of poor drug penetration, for example the brain), asymptomatic patients with slow progression may continue TKI until symptomatic [75] while rapid progressing patients may be switched to chemotherapy.…”
Section: Egfr Tki In Egfr-mutated Patientsmentioning
confidence: 99%
“…The Response Evaluation Criteria in Solid Tumors (RECIST) has been used as a standard method for assessing response and defining progression in cancer patients receiving treatment (15). However, there is more evidence every day, which suggests that continuing treatment beyond radiographic progression could confer an advantage, especially in patients treated with targeted therapy or immunotherapy (16). Treatment guidelines for NSCLC recommend continued use of TKI and local therapy after disease progression in asymptomatic patients.…”
Section: Introductionmentioning
confidence: 99%